If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -4(-3x + 18) = -132 Reorder the terms: -6x + -4(18 + -3x) = -132 -6x + (18 * -4 + -3x * -4) = -132 -6x + (-72 + 12x) = -132 Reorder the terms: -72 + -6x + 12x = -132 Combine like terms: -6x + 12x = 6x -72 + 6x = -132 Solving -72 + 6x = -132 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '72' to each side of the equation. -72 + 72 + 6x = -132 + 72 Combine like terms: -72 + 72 = 0 0 + 6x = -132 + 72 6x = -132 + 72 Combine like terms: -132 + 72 = -60 6x = -60 Divide each side by '6'. x = -10 Simplifying x = -10
| 74-1.5x+1.5x-2=72 | | 2500=1000x-800 | | 24=35+x | | 65-11=-2s+5 | | -270=-18x | | a^2=24-2 | | -12(2n+13)=-420 | | 4x-6(x-16)=114 | | 7y-2y-6+4= | | 12p-7=-3p+5 | | -(q-2+6r)=o | | -14+x=3x+30 | | x^2=567 | | 2c-b=k | | X+1.5x-2=72 | | m-3(m+2)=4(1-2m)+2 | | 14r-6(1-10r)=142 | | 9x+5-4=-20 | | -4y+24=12 | | 10x-8y=7 | | 2d-8-(8d-2)=54 | | 1.5a+5=1.167 | | -5n-1=29 | | -(-x+6)=-3x | | -8x-2y=32 | | 3+4x=7x-18 | | -68+9x=4x+27 | | 15x-10y= | | 2+3x=3x+2 | | 3x-4=2y | | 7n-7(9n+10)=-686 | | 2x-21=x+9 |